Effect of Porphyridium cruentum polysaccharides on the activity of murine macrophage cell line RAW 264.7 - R T Abdala-Diaz; M Chabrillon; A Cabello-Pasini; B Lopez-Soler; F L Figueroa (Ciencias Marinas, 2010)
Red algae are considered an important source of polysaccharides with potential immunomodulatory properties. Polysaccharides from the cell wall of the red alga Porphyridium cruentum can compose more than 50% of its biomass; however, little is known regarding its biochemical composition and phage-modulatory properties. Consequently, this study aimed to evaluate the effect of P. cruentum polysaccharides on tumor necrosis factor-alpha (TNF-alpha), interleukin-6 (IL-6), and nitric oxide (NO) production. Polysaccharides from P. cruentum were extracted and purified by N-cetylpyridinium bromide precipitation and characterized by Fourier transform infrared spectroscopy. The effect on the activity of murine macrophage cell line RAW 264.7 was examined by quantification of TNF-alpha, IL-6, and NO production using enzyme-linked immunosorbent assays. The results showed that the polysaccharides from P. cruentum induced TNF-alpha and IL-6 cytokine accumulation. The production of TNF-alpha was significantly higher than that in the control (bacterial lipopolysaccharide, LPS) when the concentration of polysaccharides was higher than 6.25 µg mL–1. The addition of polysaccharide levels above 25 µg mL–1 produced IL-6 levels ranging from 3.4 to 4 ng mL–1, which were comparable to the production of IL-6 induced by 50 ng mL–1 of LPS (3.3 ± 0.3). In contrast to IL-6 and TNF-alpha, NO production was only detected when polysaccharide concentrations were higher than 25 µg mL–1. These results indicate for the first time that polysaccharides from P. cruentum are strong cytokine inducers.